Sanhuang Fukang oil alleviates X-ray-induced skin injury by reducing inflammation and apoptosis: an in vivo study - Zhu, Ruochen; Lin, Mandi; Deng, Wei; Jian, Xintong; Chen, Chiwei; Shi, Xinlei; Lai, Milin; Huang, Mei (Frontiers in Pharmacology, 2026)
BackgroundRadiation dermatitis is a significant dose-limiting toxicity of radiotherapy that compromises treatment efficacy and patient quality of life. Although topical anti-inflammatory agents and emollients provide symptomatic relief, they fail to address the underlying pathophysiological mechanisms. SHFKO, a botanical extract with documented antioxidant and anti-inflammatory properties, has been used in traditional medicine but its molecular mechanisms of action remain poorly characterized. This study systematically investigated the therapeutic potential of SHFKO in mitigating radiation-induced skin injury through integrated chemical, molecular, and histopathological analyses.MethodsUltra-performance liquid chromatography (UPLC) was used to characterize the bioactive components of SHFKO. A mouse model of radiodermatitis was monitored for cutaneous manifestations and healing. Expression levels of inflammatory mediators (MMP13, IL-6, IL-1β), antioxidant enzymes (catalase, HO-1, SOD-1, Nrf2), and apoptotic regulators (cleaved-caspase 3, Bcl-2) were measured using RT-PCR and Western blotting to assess radiation-induced oxidative stress and apoptosis. The effects of SHFKO on MAPK/NF-κB/PI3K-AKT signaling pathways were evaluated by Western blotting and immunohistochemistry.ResultsUPLC analysis confirmed a diverse bioactive profile of SHFKO. In vivo experiments demonstrated significant attenuation of cutaneous inflammation and enhanced tissue regeneration. RT-PCR and Western blot analyses revealed dose-dependent anti-inflammatory effects of SHFKO, with the high-dose treatment achieving effects comparable to the reference drug, MFC (p > 0.05). Mechanistic studies revealed pathway-specific modulation, with anti-radiodermatitis effects primarily mediated by inhibition of MAPK/PI3K-AKT phosphorylation rather than the NF-κB pathway. Immunohistochemical staining confirmed that SHFKO normalized the radiation-induced upregulation of MMP13, IL-6, IL-1β, integrin β1, and CXCL9. Additionally, SHFKO exhibited anti-apoptotic activity, which accelerated cutaneous repair.ConclusionThis study demonstrated significant therapeutic effects of SHFKO in treating radiodermatitis, characterized by accelerated healing of acute radiation-induced cutaneous injuries. The multi-targeted mechanisms involved apoptosis inhibition, reduction of pro-inflammatory mediators, MAPK/PI3K-AKT pathway inhibition, and restoration of ROS homeostasis. These findings suggest SHFKO as a promising candidate for clinical development in radiation dermatitis treatment, offering a multi-target therapeutic approach distinct from conventional approaches.